Direct Growth of Vertically-Aligned Single-Walled Carbon Nanotubes on Conducting Substrates using Ethanol for Electrochemical Capacitor - Mohd Abid, Mohd Asyadi Azam (École Polytechnique de Montréal, Canada, 2011)
A massive growth of vertically-aligned single-walled carbon nanotubes (VA-SWCNTs) from aluminum oxide (Al-O)-supported Co catalyst and high purity ethanol was performed using alcohol catalytic chemical vapor deposition (ACCVD) technique. SWCNTs with 50-μm thickness were grown on the substrates via this technique. The Al metal layer of 20 nm thickness was thermally-oxidized for the production of Al-O, and 0.5 nm cobalt (Co) thin films was used as catalyst for the CVD process. The CNT growth was optimized using SiO2/Si substrates, and similar experimental condition was applied to the conducting substrates. The as-grown CNTs were characterized using Raman spectroscopy and electron microscopies for growth confirmation and for quality level investigation. Development of the catalyst nanoparticles and Al-O support layer was observed using atomic force microscopy (AFM) and transmission electron microscopy (TEM). The electrodes were fabricated using directly-grown VA-SWCNTs on SUS 310S, and were successfully used as an electrochemical capacitor. Electrochemical analysis using KOH aqueous electrolyte was performed by cyclic voltammetric (CV) and galvanostatic chargedischarge measurements; a maximum 52 Fg-1 specific gravimetric capacitance was obtained from the VA-SWCNT electrodes.